Materials for total joint arthroplasty: biotribology of potential bearings - Sonntag, Robert; Kretzer, Jan Philippe (Imperial College Press, 2016)
Contents -- Preface -- 1. Bio-Tribological Demands -- 1. Description of the Bio-Technical System -- 2. Factors Influencing Longevity of Joint Replacements -- 2.1. Implant -- 2.2. Surgeon -- 2.3. Patient -- 3. Approaches for New Bearings -- References -- 2. Evolutionary History of Arthroplasty -- 1. Early Treatment of Joint Diseases -- 1.1. Interposition Arthroplasty -- 1.2. First Joint Replacements in the Late 19th Century -- 2. Early Milestones -- 2.1. Mold Hemiarthroplasty: Another Step Forward -- 2.2. The Hip Hemiarthroplasty
Includes bibliographical references and index
Keywords: Implantatwerkstoff; Gelenkendoprothese